1996
DOI: 10.1093/oxfordjournals.eurheartj.a015039
|View full text |Cite
|
Sign up to set email alerts
|

PTCA: Periprocedural platelet activation Part II of the Duesseldorf PTCA Platelet Study (DPPS)

Abstract: We conclude that PTCA can induce consumption, particularly of preactivated platelets, and lead to sustained platelet activation after the procedure. This might explain why preactivated patients are at increased risk of suffering periprocedural ischaemic events and why increased thrombogenicity favours acute flow disruption and the progression of coronary stenosis at the lesion site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 24 publications
2
14
2
1
Order By: Relevance
“…The majority of flow cytometric studies that have previously reported platelet activation following PTCA have used local sampling techniques, either from the coronary sinus [23,24] , or directly from the coronary artery [25] . In contrast to our present findings, Kolarov et al [26] , using flow cytometry in peripheral blood, reported both a significant reduction in platelet count and increased platelet activation following PTCA, but sampling was performed much earlier (2 h post PTCA), at a time when platelet behaviour might still be affected by periprocedural anticoagulation. Gawaz et al [27] showed no significant changes in platelet activation in peripheral blood samples from patients undergoing elective PTCA, although changes were observed in patients undergoing PTCA for acute myocardial infarction.…”
Section: Discussioncontrasting
confidence: 99%
“…The majority of flow cytometric studies that have previously reported platelet activation following PTCA have used local sampling techniques, either from the coronary sinus [23,24] , or directly from the coronary artery [25] . In contrast to our present findings, Kolarov et al [26] , using flow cytometry in peripheral blood, reported both a significant reduction in platelet count and increased platelet activation following PTCA, but sampling was performed much earlier (2 h post PTCA), at a time when platelet behaviour might still be affected by periprocedural anticoagulation. Gawaz et al [27] showed no significant changes in platelet activation in peripheral blood samples from patients undergoing elective PTCA, although changes were observed in patients undergoing PTCA for acute myocardial infarction.…”
Section: Discussioncontrasting
confidence: 99%
“…Since leukocytes and platelets were obtained from the coronary sinus before and immediately after successful intervention, our findings may reflect a consumption of activated platelets and leukocytes during the procedure at the site of vessel injury. A loss of activated platelets during percutaneous transluminal coronary angioplasty has been reported [11]. It was suggested that circulating preactivated platelets aggregate and immediately respond to the performed manipulations [11].…”
Section: Discussionmentioning
confidence: 99%
“…To analyze platelet adhesion proteins, blood was drawn from the coronary sinus and immediately fixed as described above [11,12]. A single-platelet flow cytometry assay was used to measure platelet activation [10][11][12].…”
Section: Assessment Of Adhesion Proteins On Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported significant platelet activation after PTCA. Kolarov et al [31] studied 25 patients receiving PTCA. For flow cytometry they used CD62p, CD63, and thrombospondin.…”
Section: Discussionmentioning
confidence: 99%